2021
DOI: 10.1038/s41598-021-82719-x
|View full text |Cite
|
Sign up to set email alerts
|

A non-bioartificial liver support system combined with transplantation in HBV-related acute-on-chronic liver failure

Abstract: We aim to determine the impact of an artificial liver support system (ALSS) treatment before liver transplantation (LT), and identify the prognostic factors and evaluate the predictive values of the current commonly used ACLF prognostic models for short-term prognosis after LT. Data from 166 patients who underwent LT with acute-on-chronic liver failure (ACLF) were retrospectively collected from January 2011 to December 2018 from the First Affiliated Hospital of Zhejiang University School of Medicine. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In the present study, NLR values after ALSS were inversely correlated with in-hospital outcomes. This conclusion agrees with other studies ( Fan et al., 2017 ; Li et al., 2021 ; Sheng et al., 2022 ). An NLR > 6.78 after ALSS treatment predicts high mortality risk.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, NLR values after ALSS were inversely correlated with in-hospital outcomes. This conclusion agrees with other studies ( Fan et al., 2017 ; Li et al., 2021 ; Sheng et al., 2022 ). An NLR > 6.78 after ALSS treatment predicts high mortality risk.…”
Section: Discussionsupporting
confidence: 94%
“…A study conducted by Zhejiang University in China reviewed data from 166 patients with chronic liver failure and ACLF over the past 8 years, and the results showed that a non-biological artificial liver support system combined with transplantation significantly improved short-term survival rates. One partial mechanism is that artificial liver treatment reduces systemic inflammation and improves the internal environment 7 . While the combination of DPMAES with PE has shown promise, it often yields unsatisfactory results in patients with C-type ACLF, PT activity less than 20%, and TBiL levels exceeding 300 umol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin adheres to the resin in the BS330, whereas the resin in the HA330-II blood perfusion device adsorbs inflammatory mediators (16). There are several reports on the application of DPMAS in adult patients with ALF but few describing its use in pediatric patients with ALF (17)(18)(19)(20)(21)(22). Furthermore, the efficacy profiles of DPMAS combined with sequential half-dose PE and single fulldose PE have not been compared.…”
Section: What Is Newmentioning
confidence: 99%